Design of an Integrated Lens for Separating Microwave and Optical Wave. Issue 10 (26th July 2013) - Che, Rongrong; Yi, Zixuan; Zhu, Qi; Xin, Hao
ABSTRACT In this article, we proposed a design of an integrated lens, which is composed of an optical Fresnel lens (OFL) and a microwave Fresnel zone plate lens (MFZPL). The MFZPL is constructed by a helices array. The OFL focuses the light wave whereas the MFZPL focuses microwave. Both, simulations and experimental results show that microwave and light wave can be converged in their respective focal regions. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2358–2363, 2013